Detection of TGF-β in pleural effusions for diagnosis and prognostic stratification of malignant pleural mesothelioma. (January 2020) - Stockhammer, Paul; Ploenes, Till; Theegarten, Dirk; Schuler, Martin; Maier, Sandra; Aigner, Clemens; Hegedus, Balazs
Highlights: Pleural effusion TGF-β levels were highly diagnostic in our MPM cohort. Both epithelioid and non-epithelioid MPM patients had high TGF-β levels. Effusion TGF-β levels correlated with disease stage and tumor volume. Combining effusion TGF-β and mesothelin led to 93.4 % sensitivity to diagnose MPM. Effusion TGF-β was found to be an independent, highly prognostic biomarker. Abstract: Objectives: Malignant pleural mesothelioma (MPM) is an aggressive malignancy with dismal prognosis but variable course of disease. To support diagnosis and to risk stratify patients, more reliable biomarkers are warranted. Emerging evidence underlines a functional role of transforming growth factor-beta (TGF-β) in MPM tumorigenesis though its utility as a clinical biomarker remains unexplored. Materials and methods: Corresponding pleural effusions and serum samples taken at primary diagnosis were analyzed for TGF-β by ELISA, and for mesothelin (SMRP) by chemiluminescence enzyme immunoassay. Tumor load was quantified in MPM patients by volumetric analysis of chest CT scans. All findings were correlated with clinicopathological characteristics. Results: In total 48 MPM patients, 24 patients with non-malignant pleural disease (NMPD) and 30 patients with stage IV lung cancer were enrolled in this study. Pleural effusions from MPM patients had significantly higher TGF-β levels than from NMPD or lung cancer patients (p < 0.0001; AUC for MPM vs NMPD: 0.78, p = 0.0001). Both epithelioid and non-epithelioid MPM were associated with higher TGF-β levels (epithelioid: p < 0.05; non-epithelioid: p < 0.0001) and levels of TGF-β correlated with disease stage (p = 0.003) and with tumor volume (p = 0.002). Interestingly, high TGF-β levels in pleural effusion, but not in serum, was significantly associated with inferior overall survival (TGF-beta ≥14.36 ng/mL: HR 3.45, p = 0.0001). This correlation was confirmed by multivariate analysis. In contrast, effusion SMRP levels were exclusively high in epithelioid MPM, negatively correlated with effusion TGF-β levels and did not provide prognostic information. Conclusion: TGF-β levels determined in pleural effusion may be a promising biomarker for diagnosis and prognostic stratification of MPM.